Mitigating Human Impacts on Wild Animal Welfare - David W. Macdonald (Animals, 2023)
Human activities negatively impact the welfare of wild vertebrates in many different contexts globally, and countless individual animals are affected. Growing concern for wild animal welfare, especially in relation to conservation, is evident. While research on wild animal welfare lags behind that focused on captive animals, minimising human-induced harm to wild animals is a key principle. This study examines examples of negative anthropogenic impacts on wild animal welfare, how these may be mitigated and what further research is required, including examples from wildlife management, biodiversity conservation, wildlife tourism and wildlife trade. Further, it discusses the relationship between animal welfare and biodiversity conservation, and synergies that may be achieved between these. Ultimately, it is discussed how the welfare of wild animals may be balanced with other priorities to ensure that welfare is afforded due consideration in interactions between people and wildlife.